ANALISIS LITERASI STATISTIS DITINJAU PENGETAHUAN AWAL DAN SELF ESTEEM MATEMATIS MAHASISWA - Pamungkas, Aan Subhan; Khaerunnisa, Etika; V Y, Indhira Asih; Yuhana, Yuyu (Journal of the Indonesian Mathematics Education Society, 2020)
Statistical Literacy is the ability of individuals to formulate, apply and interpret statistics in various contexts. This ability is very important possessed by students as a tool to solve problems when doing research or solve problems related to statistics. The ability of a person’s statistical literacy is influenced by several factors such as prior knowledge and mathematical self esteem. So by optimizing these two factors, then the statistical literacy ability of students will develop well Based on these assumptions, this study aims to examine students’ statistical literacy in terms of early knowledge and mathematical self esteem in basic statistics courses. Based on the purpose of the research, this research is descriptive quantitative research. Population as well as samples in this study are all students of Primary Education of Sultan Ageng Tirtayasa University Academic Year 2019/2020 which amounted to 34 students. Data collection techniques use test of statistical literacy, test of early knowledge and mathematical self esteem scales. Data analysis in this research use descriptive and inferential statistic analysis. Based on the results of data analysis showed that (1) The mean of the prior knowledge (PK) of students that is equal to 9.79 (average), consists of a group of 10 students high prior knowledeg, 14 students average prior knowledge and 10 students low prior knowledge; (2) the mean of student’s mathematical self esteem of 65,38 (average), consist of high mathematical self esteem group as many as 12 students, 14 students average mathematical self esteem and 8 students low mathematical self esteem; (3) the average of statistical literacy ability 58,68 with average category; (4) There is a significant difference of students’ statistical literacy in terms of prior knowledge category (high, average, and low); (5) there is a significant difference of students’ statistical literacy in terms of student’s mathematical self esteem category (high, medium, low).